IMPLEMENTASI KEBIJAKAN JAMINAN KESEHATAN DAERAH (STUDI KASUS JKSS DI KABUPATEN BANGKA) - Zenderi Wardani (Jurnal Paradigma (JP), 2017)
Jaminan Kesehatan Sepintu Sedulang (JKSS) is a form of public policy in improving basic services as mandatory government affairs to public in the regional autonomy era financing from local budget (APBD). This policy was approved by the Decree of Bangka District No. 188.45/236/Kes/2005. There are many obstacles in implementing this policy. Then these obstacles become the research focus to see the implementation process base on the policy content and implementation context in basic health services and referral.To improve the implementation of this policy more effective and efficienct, some suggestions can be considered such as implementation of an appropriate capitation system, strengthening human resources and organization or the implementing agency (Bapel) it self separately as legal basis in implementing this policy to be local regulation (Perda).